Detecting 5-methylcytosine using an enzyme-free DNA strand exchange reaction without pretreatment under physiological conditions. Issue 41 (3rd May 2016) - Xu, Chen; Wu, Jinjun; Liu, Wenting; Hong, Tingting; Wang, Tianlu; Zhang, Xiaoe; Fu, Boshi; Wu, Fan; Wu, Zhiguo; Zhou, Xiang
Abstract : We present here a novel and efficient method for 5mC detection using a DNA strand exchange reaction (SER) strategy. Abstract : We present here a novel and efficient method for 5mC detection using a DNA strand exchange reaction (SER) strategy. This enzyme-free method needs no pre-treatment of target DNAs and can be adapted to most of the target duplexes under physiological conditions. The high sequence selectivity of this method can distinguish 5mC from normal cytosine in an accurate manner.